Henry O. Severance scrapbook - Severance, Henry O. (Henry Ormal), 1867-
Scrapbook, compiled by Severance, containing clippings, postcards, photographs, and other material relating to Port Austin, Mich.
Librarian.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Michigan -- History, Local; Port Austin (Mich.) -- History; Librarians